1989
DOI: 10.1172/jci114102
|View full text |Cite
|
Sign up to set email alerts
|

Androgen regulation of rat renal angiotensinogen messenger RNA expression.

Abstract: Renal angiotensinogen (ang-n) mRNA concentration in the male WKY rat increases significantly during puberty. Furthermore, renal angiotensinogen mRNA level in the adult female WKY rat is considerably lower than in the male. The present study investigates the role of androgen in differential renal ang-n mRNA expression. Northern and slot blot analyses with a-32P labeled ang-n cDNA (pRang 3) demonstrated that castration lowered ang-n mRNA levels in the male kidney by 2 60% compared with control, suggesting that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
120
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(128 citation statements)
references
References 22 publications
8
120
0
Order By: Relevance
“…Studies by 2 independent laboratories have shown that androgens increase and castration decreases renal mRNA expression of angiotensinogen, the substrate for renin. 15,16 In our studies, PRA was found to be significantly reduced in castrated males when compared with either young males or old intact males. A reduction in PRA and thus angiotensin II is one mechanism by which glomerular capillary pressure could be reduced and renal function and morphology protected.…”
Section: Fortepiani Et Al Aging Androgens and Renal Injurysupporting
confidence: 49%
“…Studies by 2 independent laboratories have shown that androgens increase and castration decreases renal mRNA expression of angiotensinogen, the substrate for renin. 15,16 In our studies, PRA was found to be significantly reduced in castrated males when compared with either young males or old intact males. A reduction in PRA and thus angiotensin II is one mechanism by which glomerular capillary pressure could be reduced and renal function and morphology protected.…”
Section: Fortepiani Et Al Aging Androgens and Renal Injurysupporting
confidence: 49%
“…In female rats, testosterone treatment increases renin activity and angiotensinogen expression. 90,91 Moreover, high testosterone levels have been associated with increased vasoconstriction in sucrose-fed female rats 92 and increased levels of endothelin, a potent vasoconstrictor, in postmenopausal women. 15 Glucose and insulin metabolism Table 2 summarizes the cross-sectional and longitudinal studies that examined the association between testosterone, SHBG and markers of glucose and insulin metabolism.…”
Section: Cardiovascular Risk Factors and Diseasementioning
confidence: 99%
“…Testosterone supplementation in rats stimulates production of angiotensinogen, the substrate for renin, in the kidney, activating the RAS. 34,35 Androgen supplementation in women is also associated with increased plasma endothelin. 36 In addition, supplementation of dihydrotestosterone (10 ĻŖ9 M) in cultured mesangial cells from SHR causes an increase in oxidative stress and increases angiotensin type-1 (AT 1 ) receptor expression (Cucchiarelli and Reckelhoff, unpublished data, 2003).…”
Section: Possible Mechanisms Responsible For Postmenopausal Hypertensmentioning
confidence: 99%